A Review Of Parabolic Dish-Stirling Engine System Based On Concentrating Solar Power - Liaw, Geok Pheng; Affandi, Rosnani; Ab Ghani, Mohd Ruddin; Gan, Chin Kim; Jano, Zanariah; Sutikno, Tole (Universitas Ahmad Dahlan (UAD) and Institute of Advanced Engineering and Science (IAES), 2014)
-